Characterization of the extended Myb-like DNA-binding domain of trithorax group protein Zeste. - Mohrmann, L.; Kal, A.J.; Verrijzer, C.P. (Journal of Biological Chemistry, 2002)
Zeste is a Drosophila sequence-specific DNA-binding protein that performs a variety of functions during chromatin-directed gene regulation. Its DNA-binding domain (DBD) was previously identified, but no similarities to established DNA-binding structures are known. Here we present sequence comparisons suggesting that the Zeste-DBD is a novel variant of the tri-helical Myb-DBD. Using band shift assays, we mapped the Zeste-DBD to 76 residues, corresponding to a single Myb repeat of only 50 residues. All residues involved in formation of the hydrophobic core of the Myb domain are conserved in Zeste, suggesting it forms an extended Myb domain. Mutagenesis studies determined (T/C/g)GAGTG(A/G/c) as the consensus Zeste recognition sequence. Reconstituted transcription experiments established that deviations from this optimal consensus compromise transcriptional activation by Zeste. In addition, flanking DNA is critical because Zeste-DBD binding requires a DNA sequence of minimally 16 base pairs, which is much longer than the consensus site. The DNA flanking the consensus is contacted by Zeste through sequence-independent backbone contacts. Interestingly, hydroxyl radical footprinting revealed that the Zeste-DNA backbone contacts all map to one face of the DNA. We compare the DNA-binding properties of Zeste with those of classical tri-helical DBDs harboring a helix-turn-helix motif and suggest a model for Zeste-DNA recognition.